Situational crime prevention at nightclub entrances in Perth, Western Australia: Exploring micro-level crime precipitators - Cozens, Paul; Greive, Shane (Palgrave Macmillan, 2014)
There has been a significant increase in the use of physical security measures in Western cities over the past 30 years and situational crime prevention has become increasingly popular. During this period, the night-time economy (NTE) has become a significant area for international research. Much of the research has concentrated on investigating and regulating for improved security of nightclubs and licensed premises. Homel and Tomsen and Walker have previously argued that door security was most in need of regulation. Since then, a variety of security measures, initiatives and technology has been used to control entry points to licensed premises, including CCTV, doormen (bouncers) and identification scanners. Following Wortley’s concept of crime precipitators, it has been suggested that poor governance can inadvertently create crime precipitators at the meso, macro and micro level of the NTE. This article adopts a grounded theory approach to explore the micro-level governance of nightclub entrances in Perth, Western Australia. Using observational data collected from fieldwork over several years, the authors ask the question ‘what does the entrance “say”, about the licensed premises?’ How are different venues perceived and how might excessive security measures operate to precipitate crime?